Characterization data of reference cement CEM I 42.5 R used for priority program DFG SPP 2005 “Opus Fluidum Futurum – Rheology of reactive, multiscale, multiphase construction materials” - Lu, Z. C.; Haist, M.; Ivanov, D.; Jakob, Cordula; Jansen, Daniel; Leinitz, S.; Link, J.; Mechtcherine, V.; Neubauer, Jürgen; Plank, J.; Schmidt, W.; Schilde, C.; et al. (Data in Brief, 2019)
A thorough characterization of starting materials is the precondition for further research, especially for cement, which contains various phases and presents quite a complex material for fundamental scientific investigation. In the paper at hand, the characterization data of the reference cement CEM I 42.5 R used within the priority program 2005 of the German Research Foundation (DFG SPP 2005) are presented from the aspects of chemical and mineralogical compositions as well as physical and chemical properties. The data were collected based on tests conducted by nine research groups involved in this cooperative program. For all data received, the mean values and the corresponding errors were calculated. The results shall be used for the ongoing research within the priority program.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Characterization; DFG SPP 2005; Portland cement

Characterization data of reference cement CEM III/A 42.5N used for priority program DFG SPP 2005 “Opus Fluidum Futurum – Rheology of reactive, multiscale, multiphase construction materials” - Lu, Z. C.; Haist, Michael; Ivanov, Dimitri; Jakob, Cordula; Jansen, D.; Schmid, Marlene; Kissling, P. A.; Leinitz, S.; Link, J.; Mechtcherine, Viktor; Neubauer, Jürgen; Plank, J.; et al. (Data in Brief, 2020)
Keywords: Slag; DFG SPP 2005; Cement; Characterization

Characterization data of reference materials used for phase II of the priority program DFG SPP 2005 “Opus Fluidum Futurum – Rheology of reactive, multiscale, multiphase construction materials” - Pott, Ursula; Crasselt, C.; Fobbe, Nicholas; Haist, Michael; Heinemann, M.; Hellmann, S.; Ivanov, Dimitri; Jakob, Cordula; Jansen, Daniel; Lei, Lei; Ran, Li; Julian, Link; et al. (Data in Brief, 2023)
A thorough characterization of base materials is the prerequisite for further research. In this paper, the characterization data of the reference materials (CEM I 42.5 R, limestone powder, calcined clay and a mixture of these three components) used in the second funding phase of the priority program 2005 of the German Research Foundation (DFG SPP 2005) are presented under the aspects of chemical and mineralogical composition as well as physical and chemical properties. The data were collected based on tests performed by up to eleven research groups involved in this cooperative program.<br

Comparing Phase Development and Rheological Properties of OPC Paste Within the First Hour of Hydration - Jakob, Cordula; Jansen, Daniel; Pott, Ursula; Neubauer, Jürgen (Rheology and Processing of Construction Materials, 2020)
In this paper the very early hydration of ordinary Portland cement at 20 °C and 30 °C is investigated, focussing on the first hour after the addition of water. The development of the rheological behaviour of cement paste during hydration is compared with the kinetics determined by quantitative in-situ X-ray diffraction (QXRD) and heat flow calorimetry. For both temperatures the cumulative heat correlates very well with the evolution of ettringite content over the first hour of hydration. The precipitation rate of ettringite is strongly influenced by temperature. This results in a higher formation rate of ettringite already in the first minutes after mixing at 30 °C. Analogously the temperature affects the rheological behaviour of the cement paste. The measured torque values are also higher for 30 °C from the first point of investigation on. Furthermore, the increasing torque can be linked to the rise in the ettringite content at both temperatures. The formation of other hydrate phases influencing the development of the rheological behaviour within the observed time frame cannot be proven with the data at hand. Therefore, it can be assumed that ettringite content is the determining mineral for the early workability of cement pastes.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Ettringite formation; Hydration kinetics; OPC; Rheology; Temperature

Comparison of physical and physicochemical methods for 3D printing application with the focus on the unconfined uniaxial compression test - Pott, Ursula; Jakob, Cordula; Wolf, Julian; Stephan, Dietmar (Construction and Building Materials, 2023)
For a commercial success of 3D concrete printing, standardisation is necessary to enable industrial production. To select methods for standardisation from the material side, detailed knowledge of suitable methods and of material behaviour is required in advance. Therefore, this study aims to compare different methods for investigating stiff printable mortars during the transition regime of a non-Newtonian fluid to a cohesive frictional material by physical and physicochemical methods focusing on the unconfined uniaxial compression test. The study shows that all methods exhibit comparable progressions, although the results are affected differently by self-heating, material composition and progressive hydration.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Apparent static and dynamic Young's modulus; Early age mortar properties; Green strength; In-situ QXRD; Isothermal heat flow calorimetry; Slow penetrating sphere test; Ultrasonic wave transmission test

Controlling ettringite precipitation and rheological behavior in ordinary Portland cement paste by hydration control agent, temperature and mixing - Jakob, Cordula; Jansen, Daniel; Dengler, Joachim; Neubauer, Jürgen (Cement and Concrete Research, 2023)
The influence of ettringite precipitation on the rheological properties during the initial and the induction period of ordinary Portland cement (OPC) hydration is examined by combining quantitative X-ray diffraction (QXRD), thermogravimetry (TG), calorimetry, penetration test method and 1H-TD-NMR. This allows a good overview about mineralogical changes during hydration and conclusions about their effect on rheological and microstructural changes within the paste. The reaction kinetic are controlled either by varying curing temperature or by an organic additive, which allows adjustment of the initial aluminate reaction while delaying the silicate reaction for hours. A significant correlation of ettringite content and rheological behavior due to structural build-up of the paste is observed in all investigated systems. The potential influence of ettringite content on structural build-up of the paste is found to be comparable to the effect of solid volume fraction on rheology (viscosity & yield stress).
CRIS-Team Scopus Importer:2023-01-27
Keywords: Ettringite; Hydration kinetics; OPC; Organic additive; Rheology

Hydration of a 2-component CSA-OPC-mix – timing of component blending & setting on demand - Jakob, Cordula; Rudolph, Jennifer; Wolf, Julian Johannes; Neubauer, Jürgen (Advances in Cement Research, 2024)
With the ongoing development of new technologies like 3D printing, the requirements for the performance of cementitious materials become more complex. Setting on demand, while the workability of the material is retained until placement, is an important aspect of this usage. A ternary CSA-OPC-C system was developed to achieve setting on demand in a 2-component setup, where two retarded cementitious components were mixed after specific times of storage. The kinetics of the individual systems and the blend were examined by heat flow calorimetry, quantitative X-ray diffraction and pore water analysis. The rheological development was monitored by a penetration test method. The results show that the performance of the blend is independent of the storage time of the individual components and can be tailored by changes in the retarder dosage in the individual components. The initial reaction in the blend is characterized by the simultaneous dissolution of ye’elimite and C3S, resulting in the formation of ettringite as the sole detectable hydrate phase. The fate of silicon remains unclear as with the methodology at hand no silicon incorporating hydrate phase can be identified.
CRIS-Team Scopus Importer:2024-06-21
Keywords: 3D-printing Cement short-hand notation is used throughout where C = CaO; H = H; Cement/cementitious materials; Diffraction (X-ray; neutron; electron); Ettringite; Rheological/rheological properties

Investigation of a shotcrete accelerator for targeted control of material properties for 3D concrete printing injection method - Pott, Ursula; Jakob, Cordula; Dorn, Tobias; Stephan, Dietmar (Cement and Concrete Research, 2023)
The efficiency of 3D concrete printing significantly depends on the mortar performance, which can be improved and controlled by adding a shotcrete accelerator. This targeted control is implemented by adding a small accelerator dose to an injection nozzle before extrusion. In this article, a study is conducted on the suitability of the material for this application. For this purpose, a shotcrete accelerated printable mortar is investigated. Comparing physical and physicochemical results leads to an in-depth understanding of the chemical processes and their effects on physical behaviour, which enables a positive assessment of the accelerator for 3D concrete printing injection method.
CRIS-Team Scopus Importer:2023-07-28
Keywords: 3D concrete printing injection method; Cement hydration; Physical material behaviour; Shotcrete accelerator; Suitability study

Investigation of the Early Cement Hydration with a New Penetration Test, Rheometry and In-Situ XRD - Pott, Ursula; Ehm, Clemens; Jakob, Cordula; Stephan, Dietmar (Rheology and Processing of Construction Materials, 2020)
To gain more information about the relationship between early cement hydration and rheological behavior of the corresponding cement paste, a new penetration test device, with the name “Multipurpose Incremental Loading device” (MILD), has been developed. The construction and the mechanical properties of the device are described in detail. Furthermore, the implementation of a measurement and first results will be discussed, and the new device is compared with the standardized Vicat test. In addition, a comparison of the measurement results with rheological investigations is made and the results of quantitative in-situ XRD and calorimetry are integrated for a deeper understanding. We show that it is possible to get more information about the structure formation with the new device than with the Vicat test. Moreover, a comparison with the rheological properties of a cement paste was done. Both methods show two periods with different rheological behavior. During the first two hours the paste shows a slow increase of viscosity which is followed by a strong increase. The results of the penetration test and the rheometer are linked with the formation of hydration products and the heat flow development. This comparison shows that the link between the two periods is the beginning of the acceleration period. Finally, it is concluded that it is possible to get precise information about the early cement hydration with a penetration test.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Early cement hydration; Penetration test; Phase formation; Rheology

Investigation of the incompatibilities of cement and superplasticizers and their influence on the rheological behavior - Pott, Ursula; Jakob, Cordula; Jansen, Daniel; Neubauer, Jürgen; Stephan, Dietmar (Materials, 2020)
The rheological behavior of cement paste and the improvement of its flowability takes center stage in many research projects. An improved flowability can be achieved by the addition of superplasticizers (SP), such as polycarboxylate ethers (PCE). In order to be able to use these PCEs effectively and in a variety of ways and to make them resistant to changes in the environment, it is crucial to understand the influence of SPs on cement hydration. For that reason, the topic of this paper was the incompatibility of a specific SP and an ordinary Portland cement (OPC). The incompatible behavior was analyzed using rheological tests, such as the spread flow test and penetration test, and the behavior was compared by means of an ultrasound technique and explained by the phase content measured by in-situ X-ray diffraction (XRD) the heat evolution measured by calorimetry, and scanning electron microscope (SEM) images. We showed that the addition of the SP in a high dosage led to a prevention of the passivation of the most reactive and aluminum-containing clinker phases, aluminate and brownmillerite. This induced the aluminate reaction to take place in the initial period and led to an immediate stiffening of the cement paste and, therefore, to the complete loss of workability. The results showed that in addition to the ettringite, which began to form directly after water addition, hemicarbonate precipitated. The fast stiffening of the paste could be prevented by delayed addition of the SP or by additional gypsum. This fast stiffening was not desirable for SPs, but in other fields, for example, 3D printing, this undesirable interaction could be used to improve the properties of printable mortar.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Calorimetry; Hydration; In-situ XRD; Incompatibility of superplasticizer; Penetration; Rheology; SEM; Spread flow test; Ultrasound

Relating ettringite formation and rheological changes during the initial cement hydration: A comparative study applying XRD analysis, rheological measurements and modeling - Jakob, Cordula; Jansen, Daniel; Ukrainczyk, Neven; Koenders, Eddie; Pott, Ursula; Stephan, Dietmar; Neubauer, Jürgen (Materials, 2019)
In order to gain a deeper understanding of the rheological development of hydrating ordinary Portland cement (OPC) pastes at initial state, and to better understand their underlying processes, quantitative X-ray diffraction (XRD) analysis and rheological measurements were conducted and their results combined. The time-dependent relation between phase development and flow behavior of cement paste was investigated at two different temperatures (20 and 30 °C), over a period of two hours. Regarding the phase development during hydration, ettringite precipitation was identified as the dominant reaction in the first two hours. For both temperatures, the increasing ettringite content turned out to correlate very well with the loss of workability of the reacting cement paste. An exponential relationship between ettringite growth and flow behavior was observed that could be explained by applying the Krieger-Dougherty equation, which describes the influence of solid fraction on the viscosity of a suspension.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Ettringite formation; Hydration kinetics; Modeling; OPC; Rheology; Scanning electron microscopy (SEM); Temperature

Thixotropy of superplasticized cement pastes – Underlying mechanisms considering the polycarboxylate molecular structure, interparticle interactions and hydration kinetics - Nicia, David; Jakob, Cordula; Jansen, Daniel; Ivanov, Dimitri; Mazanec, Oliver; Dengler, Joachim; Neubauer, Jürgen; Lowke, Dirk (Cement and Concrete Research, 2023)
This paper deals with the decisive mechanisms of thixotropic structural build-up in superplasticized cement-based suspensions related to the PCE molecular structure. We investigate the effect of the side chain length and anionic charge ratio of tailored PCE superplasticizers on thixotropic structural build-up under quantitative consideration of colloidal and contact interactions as well as very early hydration kinetics. The thixotropic structural build-up of superplasticized cement pastes with systematically varying the PCE molecular structure was investigated at constant workability, i.e. dynamic yield stress, by adjusting the individual PCE dosage. Thixotropy was quantified using plate-plate rheometry, while at the same time superplasticizer adsorption, specific surface area, granulometric measurements and quantitative XRD analysis provided an experimental basis for the identification of the respective contribution to the structural build-up. Our results show that the thixotropic structural build-up increases with decreasing PCE side chain length and increasing anionic charge ratio. This is due to accelerated very early hydration kinetics, causing an increase in the specific surface area. The latter is primarily attributed to ettringite, modifying the particle size distribution of the hydrated cement paste. Our approach of separating the colloidal and contact interactions indicates that the PCE-induced change in particle size distribution due to accelerated ettringite formation as well as the change in the average effective layer thickness are the dominant mechanisms for the thixotropic structural build-up in this context.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Hydration kinetics; Interparticle interactions; Polycarboxylate superplasticizers PCE; Rheology of cement-based suspensions; Thixotropic structural build-up